Relationship between metabolically healthy overweight/obesity and risk of type 2 diabetes in different ethnicity: a prospective cohort study in southwest China - Wang, Xin; Wu, Yanli; Wang, Yiying; Zhou, Jie; Liu, Tao (BMC public health, 2024)
To estimate and compare the association between metabolically healthy overweight/obesity (MHO) and the risk of type 2 diabetes (T2DM) among different ethnic groups in southwest China, while also exploring possible ethnic differences. This is a prospective cohort study of 6,820 participants in Southwest China. MHO was defined as body mass index (BMI) ≥ 24 kg/m and the presence of ≤ 1 component of metabolic syndrome. Cox proportional risk models were utilized to analyze the association between MHO and the risk of T2DM. The median follow-up time was 6.58 years, during which 708 new cases of T2DM were diagnosed. In the total population, after adjusting for confounding factors, MHO was found to increase the risk of T2DM compared to metabolically healthy normal weight (MHNW) individuals (HR = 1.49, 95% CI: 1.15-1.93). Subgroup analysis by ethnicity revealed that, MHO increased the risk of T2DM in the Han population (HR = 1.64, 95% CI: 1.21-2.23), however, the difference was not statistically significant in the ethnic minority population.The results of sensitivity analysis further supported the robustness of these findings. Meanwhile, stratified by sex, age, and urban/rural, it was found that ethnic differences in the association between MHO and T2DM still existed, however, it is important to note that the association between MHO and T2DM was not statistically significant in the Han population subgroup aged ≥ 45 years (p > 0.05). MHO was associated with an increased risk of T2DM compared to MHNW, and there are ethnic differences. Future interventions need to be strengthened for Han Chinese key populations to reduce the risk of T2DM.